Combustion performance of Pterocarpus indicus leaves wastes briquette with rejected papaya as binding agent - Anggono, Willyanto (2021)
Pterocarpus indicus is a plant commonly found in Indonesia and it produces wastes from its leaves falling. Earlier investigation indicated that transforming these leaves into briquette could clean them and provide a new source of energy. However, the use of tapioca as binding agent in the previous study may be criticized for affecting the food availability as it is edible. To solve this issue, tapioca is substituted with rejected papaya. The briquette was then investigated to find out the best manufacturing parameters and its viability as a sustainable fuel. The optimum ratio of Ptercarpus indicus leaves waste and rejected papaya, which yield calorific value of 4338.79 Kcal/kg, is found to be 95% and 5%, respectively. Proximate and ultimate analyses corroborate the use of this briquette. Investigation of four combustion parameters (ignition time, flame temperature, combustion rate, and burning time) indicates that the best briquette is manufactured with biomass of 60 mesh size or 250 urn and compacted with hydraulic pressure of 2 MPa.